COMPARISON OF CLINICAL AND MORPHOLOGICAL CHANGES IN PERIHEMATOMAL BRAIN TISSUE IN HEMORRHAGIC STROKE - Pospishil, Y.O.; Falion, R.I.; Havryliuk, O.M.; Zhytynska, H.B.; Tumak, I.M. (World of Medicine and Biology, 2020)
Pathomorphological research changes in brain tissue in the perihematomal zone of 28 autopsies of patients with hemorrhagic stroke was examinated. It has been established that the combination of acute and chronic lesions of the vascular wall is the cause of premature death in stage I. Coagulation necrosis is a common variant of neuronal death. Hemistocytic astrocytes is significantly predominate in stages II and III. The intensity of regeneration is less pronounced and significantly increases among patients who died after 7 days after the disease. The demarcation inflammation zone in most researches reveals itself in period of early and late subacute hematoma, with the gliomesodermal capsule that forms over time.